2015
DOI: 10.1589/jpts.27.1697
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic and anaerobic exercise training in obese adults

Abstract: [Purpose] Obesity is a global health problem and is associated with a multitude of complications. This study was designed to determine changes in cardiopulmonary functions after aerobic and anaerobic exercise training in obese subjects. [Subjects and Methods] Forty obese subjects, whose ages ranged between 18 and 25 years, were divided into 2 equal groups: group A received aerobic exercise training in addition to dietary measures, and group B received anaerobic exercise training for 3 months in addition to die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…Our data showed that in overweight and obese males, VO 2peak relative to body mass increased by 26.8% and 16.0%, respectively, while females improved by 22.5% and 10.7%, respectively. Previous studies showed lesser improvements in relative to body mass VO 2peak : between 8% 33 and 17% 12 for overweight and obese individuals combining aerobic exercise with a mild hypocaloric diet, or 5% for overweight males performing aerobic or resistance training. 11 These differences could be due to the weight loss generated by our program, which was greater than in those studies.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our data showed that in overweight and obese males, VO 2peak relative to body mass increased by 26.8% and 16.0%, respectively, while females improved by 22.5% and 10.7%, respectively. Previous studies showed lesser improvements in relative to body mass VO 2peak : between 8% 33 and 17% 12 for overweight and obese individuals combining aerobic exercise with a mild hypocaloric diet, or 5% for overweight males performing aerobic or resistance training. 11 These differences could be due to the weight loss generated by our program, which was greater than in those studies.…”
Section: Discussionmentioning
confidence: 90%
“…Some found improvements in VO 2peak only with aerobic and/or combined (aerobic/resistance) training, 6 , 7 , 8 , 9 , 10 whereas others also found improvements applying resistance training. 11 , 12 , 13 , 14 , 15 , 16 , 17 Aerobic training promotes changes in aerobic capacity, increasing mitochondrial oxidative capacities and capillary density in skeletal muscle, 18 whereas resistance training increases muscle mass, which should increase maximal aerobic capacity. 19 Therefore, it is reasonable to suggest that both types of training together can contribute to the improvement in cardiorespiratory fitness.…”
Section: Introductionmentioning
confidence: 99%
“…Most reported an inverse association of obesity with physical activity; one reported a positive association with total body fat [ 44 ] and two reported no significant association [ 41 , 42 ]. The remaining studies identified associations with various clinical indicators like high blood pressure [ 35 , 38 , 45 49 ], diabetes [ 46 , 50 – 52 ], bone health [ 37 , 40 , 53 ], the metabolic syndrome [ 16 , 54 ], and Vitamin D deficiency [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are many comparative studies between yoga and aerobic exercise [16], yoga and swimming [17], aerobic and anaerobic exercise [18], slow breathing and fast breathing exercise [15], breathing exercise and aerobic exercise in asthma [19,20]. But there is lack of comparative study between aerobic and breathing exercises on general health of asymptomatic population.…”
Section: Introductionmentioning
confidence: 99%